2013
DOI: 10.1093/abbs/gmt062
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor induces multidrug resistance-associated protein 1 overexpression through phosphatidylinositol-3-kinase /protein kinase B signaling pathway and transcription factor specificity protein 1 in BGC823 cell line

Abstract: Multidrug resistance (MDR) is one of the most important causes of chemotherapy failure and carcinoma recurrence. But the roles of the MDR-associated protein MRP1 in MDR remain poorly understood. Vascular endothelial growth factor (VEGF), one of the most active and specific vascular growth factors, plays a significant role in proliferation, differentiation, and metastasis of cancers. To explore the effect of VEGF on the expression of MRP1, we used recombinant human VEGF to stimulate K562 and BGC-823 cell lines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…To delineate the mechanisms underlying the enhanced chemoresistant behavior of bCSCs, we focused on Sp1 a transcription factor that regulates pivotal chemoresistance pathways. 22,23,30 Our results revealed a significant increase in the expression levels of Sp1 protein in CR primary tumors compared with CS primary tumors (Fig 3, A). Similarly, increased SP1 expression levels were observed in CR cell lines compared with their sensitive counterparts (Fig 3, B).…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…To delineate the mechanisms underlying the enhanced chemoresistant behavior of bCSCs, we focused on Sp1 a transcription factor that regulates pivotal chemoresistance pathways. 22,23,30 Our results revealed a significant increase in the expression levels of Sp1 protein in CR primary tumors compared with CS primary tumors (Fig 3, A). Similarly, increased SP1 expression levels were observed in CR cell lines compared with their sensitive counterparts (Fig 3, B).…”
Section: Resultsmentioning
confidence: 54%
“…Recently, there has been renewed interest in the development of mithramycin A and its derivatives as anticancer agents because of their ability to specifically inhibit binding of Sp1 to GC-rich DNA, 27,30,31 and to downregulate numerous genes mediating proliferation, chemoresistance, invasion/ metastasis, and angiogenesis of cancer cells Q35 . [22][23][24][25][26][27] However, there is hardly any report describing the effect of mithramycin A in bCSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess protein expression of ABC transporter C2 and G2, Western blot analysis and immunocytochemistry were performed using antibodies specific for humans, mice and rabbits; however we were unable to identify cross-reactivity with these antibodies (data not shown). Some groups have demonstrated that activated specificity protein 1 and nuclear factor-κB enhanced the expression and activities of P-gp (Liu et al, 2010;Ke et al, 2013;Li et al, 2013). Our results suggest that suppressing chemoresistance through survivin-mediated transcription factors might extend therapeutic effects by adversely affecting DNA repair and drug elimination.…”
Section: Article In Pressmentioning
confidence: 52%
“…In addition, PI3K/Akt signaling pathway is another important intracellular signaling pathway which is also involved in the drug resistance of different types of human neoplasm cells [ 13 , 14 ]. LY294002, a PI3K-specific inhibitor, has been reported to reduce the activity of the MRP1 promoter by stimulating vascular endothelial growth factor (VEGF) [ 15 ]. In addition, treatment of K562 cell line with LY294002 or Akt siRNA downregulated P-glycoprotein (P-gp) and MRP1 expression [ 9 ].…”
Section: Introductionmentioning
confidence: 99%